Direct Anterior Approach for One-Stage Bilateral Total Hip Arthroplasty in an ASA 3 Wheelchair-Dependent Woman - B. (Britt) Barvelink; J. T. (Arjan) Hooghof; R. B. G. (Roy) Brokelman (Case Reports in Orthopedics)
This case report involves a 79-year-old wheelchair-dependent woman with bilateral destructive coxarthrosis, requiring total hip arthroplasty (THA). Mobilization and transfers were unbearable due to the bilateral involvement of her hips. Performing unilateral THA would not be sufficient due to the coexisting pain from the contralateral side. Therefore, the decision was made to perform bilateral THA in one stage using the direct anterior approach (DAA). One-stage bilateral THA (1-SBTHA) using the DAA in ASA 3 patients is not previously described in the literature. The procedure was completed as planned, without any major perioperative complications. Eight weeks postoperatively, the patient was able to mobilize unaccompanied using a walker. She regained her mobility and independence. This outcome suggests that 1-SBTHA using DAA can be considered for disabling coxarthrosis in carefully selected ASA 3 patients. DAA is the superior approach for 1-SBTHA, due to decreased muscle damage leading to early mobilization with improved gait. Another benefit of DAA is that both hips can be draped simultaneously without repositioning the patient during the procedure.